Principles of Mathematical Economics - Vali, Shapoor; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2014)
Under the assumption of a basic knowledge of algebra and analysis, micro and macro economics, this self-contained and self-sufficient textbook is targeted towards upper undergraduate audiences in economics and related fields such as business, management and the applied social sciences. The basic economics core ideas and theories are exposed and developed, together with the corresponding mathematical formulations. From the basics, progress is rapidly made to sophisticated nonlinear, economic modelling and real-world problem solving. Extensive exercises are included, and the textbook is particularly well-suited for computer-assisted learning.
Household Expenditure -- Variables, a Short Taxonomy -- Sets and Functions -- Market Equilibrium Model -- Rates of Change and the Derivative -- Optimal Level of Output and Long Run Price -- Nonlinear Models -- Additional Topics in Perfect and Imperfect Competition -- Logarithmic and Exponential Functions -- Production Function, Least-Cost Combination -- Economic Dynamics -- Mathematics of Interest Rates and Finance -- Matrices and Their Applications.
Keywords: Economics; Mathematics; Economics/Management Science; Economics/Management Science, general; Mathematics, general